Modelling web based socio-technical systems through formalising possible sequences of human experience - Walton, R; De Roure, D (Association for Computing Machinery, 2019)
When people interact through technical infrastructure such as that of organisations or the World Wide Web, this infrastructure will change and in some cases new identifiable structures or even eco-systems may emerge. Examples of such emergent socio-technical systems on the Web include some social machines and phenomena such as echo chambers. To model these complex social systems we develop a method for formalising the moments, or occasions, of experience of an individual person by contriving a 'chemistry' encoding possible sequences of their external stimuli, internal experience and reactions to this internal experience. We take a process oriented approach and formalise this as a stochastic Petri net. We wire together a number of these to form a fixed social network in which experience is shared. The resulting model unfolds into many possible causal graphs of occasions of experience which we show using an interactive visualisation. We demonstrate the utility of this method by encoding models exhibiting information diffusion and what we call multiple phase diffusion, and then consensus formation, before encoding a mechanism of echo chamber formation. We then demonstrate the conflation of individuals' positions on otherwise separate issues through emotion. The approach results in a single Petri net model which may be analysed using qualitative and quantitative techniques supporting web science research. It provides a way to describe and reason about the internal experience of individuals within multi-scale socio-technical systems.